AUDIT IN PURCHASES - Olga A. Lupinina (Plekhanov Russian University of Economics, 2017)
The article deals with the results of revealing violations in purchases; the procedure was conducted by municipal control and account bodies in 2016. Standard sources that play a key role in audit and determine methodology of assessing efficiency and effectiveness of using budget funds were enumerated. Analysis of their practical application allowed the authors to identify those spheres, where violations constantly take place and at the same time to formulate principle causes of violations that were disclosed during control sessions. The article gives a list of steps and suggestions aimed at improving the control system on the basis of regional control and account bodies’ practice.